Revealing the invisible: The virus is looking at you. Issue 1 (1st June 2021) - Barker, Garry
At the core of the various messages that have been sent out about the Coronavirus is how to deal with an invisible threat. Revealing the invisible is however an ancient issue, one that goes back thousands of years and reoccurs throughout human history. This article is an exploration of the complex interrelationship between several long-standing visual tropes that over historical time have emerged from various cultures in response to a need to communicate invisible forces. Beginning with reflections on the poster for the International Hygiene Exhibition of 1911 held in Dresden, linking in images of an Egyptian sun god, via extramission theory and thoughts about the first drawings done through a handheld, lens-focused microscope by Robert Hooke, a series of links and interconnections are made that explore how the invisible has been represented and how the invisible virus can be read as a type of 'dark star' or anti-sun. Christian traditions of the use of unnatural colour to signify both invisible power and demonic possession and the way the Coronavirus has itself been depicted are compared to historical visual tropes such as the aureola and the mandorla as used in the Greek Orthodox Church to depict sacred moments that transcend time and space. From Buddhist and Christian uses of halos via images of sea-mines, a complex series of interconnections are revealed that are now being tapped into by Government-sanctioned information leaflets relating to the Coronavirus outbreak.